The Effect of Snacks on Periodontal Health and Dental Caries among School Going Adolescents in Western Kenya - DS, Omutimba; Rotich, Joseph K; Sang, CK (Nurture, 2011)
The state of oral health in Kenya continues to generate a lot of interest considering there has been no national oral health survey for the entire nation. The main aim of the study was to investigate the relationship between snacking behavior and the level of dental caries and periodontal health. Simple random sampling techniques were used to select the study participants. Data collection was done through self-administered questionnaires and oral examination of the 389 respondents from a total of 20 schools in Western Kenya. Snacking behavior was reported in 62.5% of the respondents. Higher caries and poor periodontal health reported in those who didn’t take snacks. The risk of poor periodontal health was 1.7 times more likely in those who didn’t take snacks.